Book review: Pete Ward and Knut Tveitereid (eds.). The Wiley Blackwell Companion to Theology and Qualitative Research, ed. by Pete Ward and Knut Tveitereid (Tidsskrift for Praktisk Teologi, 2023)
Book review of Pete Ward and Knut Tveitereid (eds.). The Wiley Blackwell Companion to Theology and Qualitative Research, ed. by Pete Ward and Knut Tveitereid.